Wetland Management Affects the Dynamic of Macrophytes Decomposition in the Lagoons of Palo Verde National Park, Guanacaste - Montemarano, Justin J. (2012)
Within the wetland complex at Palo Verde National Park -Costa Rica- dominance by the native cattail Typha domingensis has prompted management efforts to reduce cattail coverage to facilitate migratory and resident waterfowl populations (e.g., Black-Bellied Whistling Duck). As a result, large areas of open water are created within the wetland complex and are colonized by a variety of macrophyte species, including the invasive water hyacinth Eichhornia crassipes. Given that decomposition of plant material is an important source of energy and nutrients in freshwater wetlands, this study aimed to investigate indirect effects of cattail management on wetland plant decomposition dynamics by examining decomposition of T. domingensis (TD) and E. crassipes (EC).  10-g of air-dried TD and EC litter in one of two states (freshly collected and dry, dead litter from the previous wet season [past season]) was placed into 3-mm mesh plastic bags. Bags were attached to posts within one of two habitat types (open water habitat and Typha-dominated habitat [N = 5]), and decomposition bags from each litter type and habitat were collected 7, 14, 34, 76 and 134 d after initial placement. Upon collection, mass loss and changes in tissue chemistry were determined. Decomposition rates were estimated by fitting the exponential decay model to mass loss data and examining litter species, litter state and habitat effects on the decay constant k.Although no differences were detected in decomposition rates between habitat types, rates were reduced in TD litter compared to EC litter and were reduced for EC litter from the past season compared to freshly senesced litter; however, litter state had no effect on TD litter decomposition rates (litter species: P = 1.4 X 10-9; litter state: P =  0.03; habitat:  P = 0.86).  Patterns of lignin content and C:N ratio correlated with decomposition rates, and may drive reduced decomposition rates in TD litter compared to EC litter.  Removal of living T. domingensis from the Palo Verde wetland may result in earlier depletion of litter in managed areas, where E. crassipes dominates, compared to in Typha-dominated habitat, where T. domingensis litter may remain as structure and a carbon source further into the season.